Cytogenetic and molecular identification of novel wheat-Elymus sibiricus addition lines with resistance to leaf rust and the presence of leaf pubescence trait - Motsnyi, Ivan I.; Halaiev, Oleksii V.; Alіeksіeіeva, Tetiana G.; Chebotar, Galyna O.; Chebotar, Sabina V.; Betekhtin, Alexander; Hasterok, Robert; Armonienė, Rita; Rahmatov, Mahbubjon (Frontiers in Plant Science, 2024)
Emerging new races of leaf rust (Puccinia triticina Eriks) are threatening global wheat (Triticum aestivum L.) production. Identifying additional resistance genes from all available gene pools is crucial to expanding wheat resistance to these virulent leaf rust races. Siberian wild rye (Elymus sibiricus L.) possesses numerous beneficial traits that can be valuable in wheat improvement. Three new wheat-E.sibiricus addition lines, O27-2 (BC8), O27-3 (BC12) and O193-3 (BC12), were developed through a backcrossing scheme in this study, using leaf rust field evaluations, molecular marker assays and cytogenetic analysis. These three lines were derived from progeny of the bread wheat cultivar 'Obriy' (2n = 6x = 42, AABBDD) and partial octoploid amphiploid wheat-E. sibiricus (2n = 8x = 56, AABBDDS t S t ). The lines (O27-2, O27-3 and O193-3) demonstrated strong specific leaf pubescence (hairiness) and resistance at the adult stage to a local population of leaf rust races. The response to leaf rust in these three lines significantly differed from that of the Lr24 gene, providing evidence for a distinct resistance mechanism associated with the 3S t chromosome. This study is the first to report the transfer of an E. sibiricus chromosome into wheat that confers leaf rust resistance. Molecular marker analysis and genomic in situ hybridisation confirmed that lines O27-2, O27-3 and O193-3 each possess one pair of E. sibiricus 3S t chromosomes. The resistance gene was determined to be on the additional alien chromosome in these lines. Molecular markers (Xwmc221, Lr29F18, Sr24/Lr24#) confirmed that the lines O27-2, O27-3, and O193-3 each contain a pair of E. sibiricus 3S t chromosomes carrying leaf rust resistance genes. These findings demonstrate that the E. sibiricus 3S t chromosome carries the leaf rust resistance gene and that the O27-2, O27-3, and O193-3 lines can serve as novel germplasm sources for introducing this resistance into wheat breeding programs. This study contributes to broadening the genetic diversity of resistance genes available for combating leaf rust in wheat.